RAPD Markers Linked to Late Blight Resistance in Tomato - Joshi, Bal K; Panthee, Dilip R; Louws, Frank J; Yencho, G Craig; Sosinski, Bryon; Arellano, Consuelo (Nepal Journal of Science and Technology, 2013)
Identification of marker is the prerequisite for marker assisted selection (MAS) and is also very effective for gene pyramiding. Bulked Segregant Analysis (BSA) technique was used to identify RAPD markers linked to the late blight disease (caused by Phytopthora infestans (Mont. de Bary) resistance in tomato using F2 population generated by crossing tomato inbred lines, NC 85L-1W(2007) which is resistant to late blight and NC 839-2(2007)-1 which is susceptible to it. A total of 250 F2 plants, and 10 plants each of the parents and F1 were used for BSA. Transgressive segregation was observed for late blight resistance. The segregation of susceptible and resistance perfectly fit the expected ratio of 3:1, that means resistance is governed by single recessive gene. Only 34 RAPD primers (17.26%) were found polymorphic between parents. Sixteen RAPD primers (47%) out of 34 gave polymorphic bands between resistant and susceptible bulks of the late blight. Four RAPD primers, namely MRTOMR-026, MRTOMR-031, MRTOMR-038 and MRTOMR-046 were identified as linked markers to loci related to late blight disease. Among those, two were linked to susceptible and two to resistance. Because of low reproducibility and dominant nature of RAPD, these markers need to be converted to SCAR markers. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 1-14 DOI: http://dx.doi.org/10.3126/njst.v14i1.8871